Artificial Intelligence and Islamic Law: Testing the Validity of ChatGPT in the Field of Zakat - Fauzul Hanif Noor Athief; Lukmanul Hakim; Tika Widiastuti; Aminullah Furqoni; Marwini (Hikmatuna : Journal for Integrative Islamic Studies, 2026)
Technological advancements have shifted the process of knowledge acquisition from textbooks and teachers to individuals independently seeking information through other source. Artificial Intelligence (AI), with ChatGPT as a natural language processing tool, has become one of these references. In Islam, the tradition of learning is emphasized through the transmission of knowledge from teachers, known as sanad, rather than through self-study or autodidacticism. This research focuses on the validity of ChatGPT's responses to user questions on the topic of zakat as one of the pillars of Islam. The study employs content analysis of answers obtained from ChatGPT and compares these responses against three primary references: Yusuf Qardawi's "Fiqh al-Zakat," Ahmad Sarwat's "Encyclopedia of Indonesian Fiqh," and the guidelines from the National Zakat Agency. The scores were determined using a 0 to 5 scoring rubric to assess the degree to which ChatGPT’s responses aligned with the primary references. The findings indicate that ChatGPT's understanding of the basic concepts of zakat has a validity score of 3.58 and a completeness score of 3.75. For the dimension of zakat objects, the validity score is 3 and the completeness score is 3.5. However, for the dimension of modern zakat, the validity score drops to 1, with a completeness score of only 0.5. Therefore, the use of ChatGPT as a learning tool for the topic of zakat should be considered a supplementary resource rather than a primary reference. Users of ChatGPT are advised to continue consulting authentic and authoritative references for deeper understanding.